Affective Organizational Commitment as a Mediating Factor for the Leader’s Support and Organizational Citizenship Behavior. - Samsudin,Asyakireen; Soffian Lee, Umi Hamidaton; Ishak, Yusniati; Ismail, Azman; Said, Suzana Muhamad; Nor, Azmawaty Mohamad (Society for Alliance, Fidelity and Advancement, 2024)
This study examines the relationships between leader’s support and organizational citizenship behavior with affective organizational commitment as a mediating variable. Self-report questionnaires were used to collect data from employees of the public election headquarters in the Klang Valley, Malaysia. The results of the SmartPLS path model analysis displayed three findings: first, relationship between leader’s support and organizational citizenship behavior was significant. Second, relationship between affective organizational commitment and organizational citizenship behavior was significant. Finally, the relationship between leader’s support and affective organizational commitment was significantly related to organizational citizenship behavior. This confirms that the effect of leader’s support on organizational citizenship behavior is mediated by affective organizational commitment in the organizational sample. Further, the study offers discussions and implications, conclusion as well as limitations and future research.